Contractualization: Will it ever end? - Tolentino, Maria Catalina C. (Philippine Journal of Labor and Industrial Relations; Vol 35 (2018): Philippine Journal of Labor and Industrial Relations, 2021)
This paper begins by presenting employment trends and proceeds to a discussion of relevant laws in the Philippine Labor Code. This paper discusses contractualization and non-standard employment that, since the advent of globalization, have become the trend, putting into doubt the gains of a globalized economy. The major issues addressed by this paper are sustainability of employment and regulating contractual arrangements. The state, as a principal actor in a tripartite industrial relations system, intervenes to mediate between the conflicting interests of labor and management to create balance among the actors. The Duterte administration has enforced stringent measures to reduce, if not end, short-term contractual work. The review of the Department of Labor and Employment (DOLE) Department Order (DO) 18-A, inspection of establishments practicing “endo” and the enforcement of DO 174 are important steps being undertaken.